Experimental and Numerical Analysis of Fatigue of PVD and CVD Coated Steels for Cold Forging Tools - Hinsel, Christian; Engel, Ulf (ICIT’97 Conference Proceedings (Int.Conf.on Industrial Tools, April 21-22,1997 Maribor, Slov) Vol. I, 1997)
None
LFT Import::2019-08-05 (1988)